2007
DOI: 10.1097/01.icl.0000226947.66077.37
|View full text |Cite
|
Sign up to set email alerts
|

A Scleral Soft Contact Lens Designed for the Postoperative Management of Pterygium Surgery

Abstract: This novel design facilitates postoperative recovery and reduces the chance of recurrence after pterygium surgery. The authors have been using this type of lens in their clinical practice for more than 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Anyways, both methods proved to be efficient in controlling postoperative pain and favoring corneal reepithelization. 163 165 Anti-inflammatory eye drops, such as corticosteroids and NSAID, and artificial tears represent commonly used molecules for controlling pain and favoring corneal healing after pterygium surgery. It has been observed that nepafenac 0.1% eye drops administered thrice a day for 3 days (in association with postoperative therapy with topical ciprofloxacin, fluorometholone, and artificial tears) provided a significant pain reduction when compared with placebo after pterygium excision with autologous conjunctival graft.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Anyways, both methods proved to be efficient in controlling postoperative pain and favoring corneal reepithelization. 163 165 Anti-inflammatory eye drops, such as corticosteroids and NSAID, and artificial tears represent commonly used molecules for controlling pain and favoring corneal healing after pterygium surgery. It has been observed that nepafenac 0.1% eye drops administered thrice a day for 3 days (in association with postoperative therapy with topical ciprofloxacin, fluorometholone, and artificial tears) provided a significant pain reduction when compared with placebo after pterygium excision with autologous conjunctival graft.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…The idea of using soft scleral lenses for therapeutic purposes is not new. Arenas and Garcia reported the use of soft scleral lenses with diameters varying from 17.5 to 19 mm for post‐operative management of pterygium. Silicone hydrogels are frequently used to treat recurrent corneal erosions and persistent epithelial defects or to facilitate epithelial healing after PRK .…”
Section: Discussionmentioning
confidence: 99%
“…This will permit the introduction of a special 18-mm diameter cannula to the central vitreous cavity, and aspirate approximately 1 mL of the vitreous fluid [Figure 2c and d]To maintain normal IOP, sodium hyaluronate is introduced into the AC, and a slow resection of the recipient's corneo-sclera is initiated, trying to separate the possible anterior synechias at the same time with a fine round-edged spatulaBleeding into the AC should be avoided with the use of small Weck-Cel pieces until the new AC has been formed [Figure 2e]Once the resection of the recipient's cornea reaches 180°, the AC should be restored by trying to liberate the synechias and normalize its boundary. In some cases when the lens is opaque, it should be removed in an extracapsular fashion with an intraocular lens (IOL) implantationOnce the scleral borders are completely dry and are without blood, a viscoelastic material (sodium hyaluronate) is placed over the iris surface, the donor sclero-cornea is placed and adjusted, and three 7-0 vicryl sutures are placed [Figure 2f]The fibrin glue is now prepared, and is placed with a curved jeweler's forceps under the scleral flap without moving the graft, which is allowed to remain still for 3 min [Figure 2g]The two conjunctival flaps previously prepared with the mosquito forceps and 7-0 vicryl sutures are closed and anchored to the limbus of the donor's sclero-cornea [Figure 2h]A giant 22-mm soft contact lens (Surgilens ® ) is placed over the recipient's eye globe[16] [Figure 3a]The surgery is finished by placing two temporary eyelid sutures (temporary tarsorrhaphy) with 8-0 polypropylene cardiovascular suture, to partially close the eyelids [Figure 3b and c]The surgery is then completed with the eye covered with a bandage patch and an eye protection shield.…”
Section: Description Of the Surgical Proceduresmentioning
confidence: 99%
“…A giant 22-mm soft contact lens (Surgilens ® ) is placed over the recipient's eye globe[16] [Figure 3a]…”
Section: Description Of the Surgical Proceduresmentioning
confidence: 99%